2016
DOI: 10.1007/s00276-016-1714-x
|View full text |Cite
|
Sign up to set email alerts
|

An age- and gender-related three-dimensional analysis of rotator cuff transverse force couple volume ratio in 304 shoulders

Abstract: The decrease in the RCTFC muscle volume is proportional during the different stages of life, maintaining a constant ratio between its components (physiological RCTFC muscle atrophy). The time-saving segmentation method and volume ratio formula proposed in this study contribute to the management and understanding of rotator cuff tear/pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Given the previous studies on the effects of the coronal and sagittal couple forces on the functions of the rotator cuff, 6 , 12 , 13 , 20 when posterior delamination occurs, biomechanical changes and damage are expected in the posterior infraspinatus and teres minor tendon regions in this study owing to the sagittal couple force. It was judged that excess tension could be applied to the anterior subscapularis tendon owing to the collapsed sagittal pairing force.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given the previous studies on the effects of the coronal and sagittal couple forces on the functions of the rotator cuff, 6 , 12 , 13 , 20 when posterior delamination occurs, biomechanical changes and damage are expected in the posterior infraspinatus and teres minor tendon regions in this study owing to the sagittal couple force. It was judged that excess tension could be applied to the anterior subscapularis tendon owing to the collapsed sagittal pairing force.…”
Section: Discussionmentioning
confidence: 94%
“… 13 The sagittal couple force has been shown to provide anteroposterior stability through the anterior subscapularis and posterior infraspinatus and teres minor tendons. 6 , 12 , 20 Considering the above theory, if posterior delamination of the rotator cuff occurs, there is a possibility of damage to the sagittal couple force. It can be inferred that the damaged couple force may affect the anterior subscapularis tendon.…”
mentioning
confidence: 99%
“…16 The main limitation of the study by Mitterer et al 16 is the lack of a healthy control group. Additionally, although 2 studies 6,25 showed no significant differences between muscle volume of the subscapularis and infraspinatus/teres minor in healthy individuals, age differences and sample size can indeed make a direct comparison of different cohorts difficult. In the study of Piepers et al, 25 only 27 shoulders in 21 patients with a mean age of 57 years were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 16 , 33 The rotator cuff transverse force couple, which defines the balance between the forces of the subscapularis muscle and the infraspinatus and teres minor muscles, plays a crucial role in the normal kinematics of the shoulder, as it generates an antagonistic balance between anterior- and posterior-directed forces ensuring appropriate glenohumeral stability. 6 , 10 , 32 Recent studies showed a balanced transverse force couple volume ratio in healthy individuals, 6 , 25 whereas Mitterer et al 16 showed an imbalanced transverse force couple with a comparatively large subscapularis muscle volume in young patients with static posterior humeral head subluxation without osteoarthritis. A greater anterior muscle volume may cause an increased posterior force vector, contributing to the static posterior humeral subluxation.…”
mentioning
confidence: 99%
“…The IS and SSc muscles are balancing forces across the shoulder that keep the humeral head compressed and centered on the glenoid as part of a transverse force couple mechanism. 14 Even in the presence of an irreparable SS tendon tear, shoulder function can be maintained. A rat study examining the effect of SS and IS tendon detachment followed by no repair, full repair, or isolated IS tendon repair found similar kinetic abilities between animals with either a full repair or an isolated IS tendon repair.…”
Section: Discussionmentioning
confidence: 99%